Genetic Analysis on Horseshoe Crab for Phylogenetic Tree Study from Jambi, Bangka Belitung, Central Java, and East Java Province, Indonesia - Kholilah, Nenik; Kurniatami, Gabriella Tarida; Kurniasih, Eka Maya; Nursalim, Nining; Janarkho, Galank Fad’qul; Ambariyanto, Ambariyanto; Wijayanti, Diah Permata; Putro, Sapto Purnomo; Cahyani, Ni Kadek Dita (Jurnal Kelautan Tropis, 2025)
Order Xiphosura, or horseshoe crabs, are rarely found and classified as macrofossils. In Indonesian waters, there are three species: Tachypleus tridentatus, Tachypleus gigas, and Carcinoscorpius rotundicauda. The genetic analysis of their kinship, however, has been extensively unexplored. This study aims to utilize DNA barcoding, focusing on the cytochrome c oxidase subunit I (COI) locus from mitochondrial DNA and investigating the phylogenetic relationships of horseshoe crabs from the four sites (Tanjung Jabung Timur Regency in Jambi, Bangka Regency in Bangka Belitung, Demak Regency in Central Java, and Tuban Regency in East Java). Additionally, the study provides insights into the biodiversity and ecological roles of horseshoe crabs within their ecosystems and surrounding habitats. Through molecular methods, this research focuses on biodiversity analysis through Sanger sequencing and MEGA 11 software for constructing phylogenetic trees and calculating genetic distances. With a total of 22 horseshoe crabs, the DNA samples from four different sites were amplified via Sanger sequencing, targeting the COI locus and analyzing with MEGA 11. The phylogenetic tree analysis revealed two distinct species, Tachypleus gigas, and Carcinoscorpius rotundicauda, exhibiting significant genetic variation between them. A clear genetic separation between the two species was observed. Otherwise, within the C. rotundicauda species, a minor genetic variation was detected between sampling sites. Notably, the genetic composition displayed greater differences between samples from Java and Sumatra compared to differences within each island. The future research should expand the sampling size and include additional genetic markers to provide a more comprehensive understanding of the genetic diversity and evolutionary history of horseshoe crabs in Indonesian waters. Integrating ecological and environmental data could further elucidate the factors driving genetic differentiation and inform conservation strategies.